Perceived stress and self-reported bruxism in peruvian dentists: a cross-sectional occupational health study - Arcos-Gordillo, Sheyla Danitza; Mamani-Cori, Vilma; Quilca-Soto, Yessica; Arcos-Gordillo, Jose Manuel; Calcina-Asillo, Talia Paola; Yucra-Sardon, Sidgar Orlando (O Mundo da Saúde, 2026)
Occupational stress represents a growing risk among healthcare professionals, with dentists being particularly exposed to both physical and emotional demands. One of its potential clinical consequences is bruxism, defined as involuntary masticatory muscle activity that may be influenced by psychological factors. This study aimed to determine the relationship between perceived stress and self-reported bruxism in dentists in the city of Puno, Peru, during 2025. A quantitative, cross-sectional, and correlational study was conducted on a sample of 219 participants. The Stress Reactivity Index (IRE-32) and a 15-item self-report bruxism checklist were used to assess the main variables. Results showed that 38.4% of the participants experienced a high level of perceived stress, and 61.6% reported some degree of bruxism, with the mild form being the most frequent (31.9%). Spearman’s correlation analysis showed a strong positive relationship between the two variables (rho = 0.689; p < 0.001), indicating that higher levels of perceived stress are associated with greater severity of self-reported bruxism. These findings suggest a significant mutual association between the two conditions, which should be considered when designing prevention and health promotion strategies targeting the mental and musculoskeletal well-being of dental professionals. Due to the cross-sectional design, these findings should be interpreted as associations rather than causal relationships.